Industrial Sector and Development of Iraqi Economy by Kaldor’s Approach For Years (2017-2030) - Ghazi Khalil Jasim Al- Hayaly, Adel (Journal of Economics and Administrative Sciences, 2022)
The study aims to clarify the impact of growth in the industrial sector on economic growth in the Iraqi economics according to the methodology of Kaldor for (2017-2030) , taking into consideration the effect of the accumulation of capital in the calculation of growth rates in the economy through productivity estimate of Total Factor Productivity (TFP) to growth in the economy, which is why the study assumes a formula to comply with the laws of Kaldor growth models developed requirements. This study is the most important to find out the development of the laws of Kaldor among Arabic studies, especially the first and third, so that the relationship between the growth of industrial production and economic growth as represented by the overall productivity of factors of production , while employment relationship is in the non-manufacturing sector with total production of inputs (TFI). The study has concluded from the developed formulation to calculate degree of increasing in returning any production stage that the increasing degree of return comparable size when estimating the laws formats as there is a strong impact between the growth rates in industrial production and growth rates in gross domestic product